Réquiem para uma cidade: um olhar sobre as alterações do Núcleo Histórico Urbano de Bonfim - MG - Ricardo Carlos Ferreira (2014)
The propose presented in this thesis is the study of the alterations occurred in the Historic Urban Core of Bonfim, after the listed if its goods, in 1997. This incredible date, asks Bonfim´s deliberative Council of the Historic heritage for NHU listed. The historic center referred was well listed after the evaluation of its significance grade for IEPHA/MG. Although the protector´s formalizing of the Patrimonial Real State´s goods from the Municipality would be approved, a new readjustment of the urban space inaugurates its city´s presence. These interventions are made by the constructive increasing, verticalization of the new constructions, changes, mischaracterization and / or architecture models´ demolition of the NHU tumbled. In front of the mischaracterization that NHU faces, the present research wants to follow the process that results in the loss of value and its attributes. The studies also want to evaluate the intervention of the municipality public power in refering the protector´s guidelines of the tumbled edification goods. Thus, the constants information in the tumbled dossier, technical reports, pictures and other documents are presented as proof of the mischaracterizing of the reality. Still, the actions of disrespect to current legislation will be examined under the Historic Patrimonial preservation with its consequences in the sphere of the Public Ministry. Finally, imagistic signs of transformations in the urban landscape of the ancient city scenarios will be presented.